Governança Ética Para Construção De Confiança Em Sistemas De Inteligência Artificial - Carini, Lucas (2019)
In this article, it is proposed the construction of a theoretical guide to serve as a basic structure to guide ethical governance applied to artificial intelligence systems. This article argues that a key element (necessary, but not sufficient) in building trust in Artificial Intelligence systems is ethical governance ie the existence of regulation. Given the increasing pace of innovation, new and streamlined governance processes are needed to establish technical and legal guidelines. In recent years there has been a real proliferation of systems based on artificial intelligence, however, this technology is being used, without observing ethical principles which makes public confidence in these systems difficult. Therefore, the construction of a theoretical guide will guide the development of artificial intelligence systems as responsible innovations, following standards and regulations. The method used was deductive. The research technique was the bibliographical one, in secondary sources.